Investigating the effects of background noise and music on cognitive test performance in introverts and extraverts: A cross-cultural study. (May 2022) - Lim, Wilson; Furnham, Adrian; McClelland, Alastair
Previous research found that introverts performed worse than extraverts on cognitive tasks in the presence of noise or music in a Western sample but not in an Asian sample. This is a cross-cultural part replication of these studies using a Western (British; N  = 45) and Asian (Singaporean; N  = 45) sample. Participants engaged in three cognitive tests in the presence of pop songs, background noise, and in silence. It was predicted that for British participants, introverts would perform worse than extraverts on all three tasks in the presence of background sounds, and performance would be worse in the presence of background sounds than in silence, but not for the Singaporean participants. The results did not show any performance differences between the background sound conditions for any of the tests across the two samples, nor any performance differences between extraverts and introverts across the background sound conditions, with three exceptions: extraversion for the British was a significant predictor of performance on the Raven's test in the silence condition, extraversion was a significant predictor of performance for both groups on the mental arithmetic task in the silence condition, and extraversion was a significant predictor of performance for Singaporeans on the mental arithmetic task in the music condition.